2013
DOI: 10.4236/abb.2013.42024
|View full text |Cite
|
Sign up to set email alerts
|

The RAPD techniques used to assess the genetic diversity in <i>Draba dorneri</i>, a critically endangered plant species

Abstract: A successful management and preservation of the natural populations is depending on accurate assessment of genetic diversity. Knowledge of genetic diversity within a population is important for the conservation of the species. Our aim was to assess the genetic diversity in Draba dorneri Heuff. population (Brassicaceae family)-an endemic plant species of conservative interest using Random Amplified Polymorphic DNA (RAPD) technique. The plant species is strictly protected at national level as well as at internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…Such findings support the fact that there are region-specific variations, which can be clarified by a long-term soil and climatic adaptation cycle. These findings are comparable to those of [52] in their study on endemic plant species (Draba dorneri Heuff), [16] in their study on three medicinal plant species belongs to the Lamiaceae family (Nepeta septemcrenata, Ballota undulate and Teucrium polium) which grows naturally in Saint Catherine Mountain at three different altitudes (1800, 2200 and 2600 m above sea level), and [53] in their study on Commiphora wightii. All of these result indicated that there are relationship between geographical distributions and the genetic diversity.…”
Section: Phylogenetic Relationship Based On Amplified Rapd and Issr Bandssupporting
confidence: 82%
“…Such findings support the fact that there are region-specific variations, which can be clarified by a long-term soil and climatic adaptation cycle. These findings are comparable to those of [52] in their study on endemic plant species (Draba dorneri Heuff), [16] in their study on three medicinal plant species belongs to the Lamiaceae family (Nepeta septemcrenata, Ballota undulate and Teucrium polium) which grows naturally in Saint Catherine Mountain at three different altitudes (1800, 2200 and 2600 m above sea level), and [53] in their study on Commiphora wightii. All of these result indicated that there are relationship between geographical distributions and the genetic diversity.…”
Section: Phylogenetic Relationship Based On Amplified Rapd and Issr Bandssupporting
confidence: 82%
“…Moreover, endurance of little variation referred to scarcity of natural selection pressure, lessen mutation rate and short life span of P. harmala species. Knowledge of genetic diversity within a population is important for the conservation of the species Catană et al [8]. Darokar et al [19] found that all accessions of Bacopa monnieri from different locations in and around city of Pune, India formed separated group.…”
Section: Resultsmentioning
confidence: 99%
“…may facilitate more effective diversity analysis of several plants. RAPD-PCR analysis has been used to evaluate the levels of genetic variation among diverse wild cranberry clones [4], genetic diversity of climbing species of palms Sramah et al [5], genetic diversity of a medicinal and aromatic plant Teucrium polium Boulila et al [6] genetic variability among five caraway populations Laribi et al [7], in Draba dorneri vascular plant Catană et al [8], among cowpea genotypes Patil et al [9], genetic diversity and related relationships among 22 landrace of Ficus carica L. sativa AliShtayeh et al [10] and for Withania somnifera (L.) Sahu et al [11]. Variability within and among genus, species and families are based on the genetic makeup, the natural selection, human interfering and nature calamities.…”
mentioning
confidence: 99%
“…Berdasarkan analisis AFLP, ukuran keragaman genetik di dalam populasi dapat dideteksi dari jumlah lokus polimorfis, heterozigositas, dan indeks Shannon (Gudeta, 2018 (Catan et al, 2013;Ritonga et al, 2018).…”
Section: Keragaman DI Dalam Populasiunclassified